KONTRIBUSI PEMAHAMAN TEKS BERITA TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 12 PADANG - Rahmah Rahmah; Ellya Ratna (Universitas Negeri Padang, 2020)
ABSTRACT This article reveals the contribution of skills comprehension text news to writing skills text news grade students VIII SMP Negeri Padang 12. The purpose of this research there are three. First, it describes the skills of comprehension text news grade VIII SMP Negeri 12 field. Second, it describes the writing skills text news grade VIII SMP Negeri 12 field. Third, describing the contribution of the intermediate comprehension text news against writing skills text news grade VIII SMP Negeri 12 field. This research type is quantitative descriptive method. The design used in this research is the design contribution. This research population is grade VIII SMP Negeri Padang are registered on the 12th school year 2019/2020, i.e. as many as 282 students. The sample in this research are determined by proportional random sampling of 20% of the population, i.e. 53 students. Research data is a score test results intermediate comprehension text news and score the writing skills test result text news. The data obtained through two types of tests i.e. objective tests to measure the comprehension text news and performance tests to measure the skills of writing a text news. The results of the research there are three. First, the skills of writing text news grade VIII SMP Negeri Padang 12 are on good qualifications (B) with an average of 76,42. Second, comprehension text news grade VIII SMP Negeri Padang 12 are on more than enough qualifications (LdC) by the value of the average 73,95. Third, there is a contribution of comprehension in the news of text to the skills of writing news texts of class grade VIII SMP Negeri Padang 12 at 15,37%. Kata kunci: Kontribusi, Keterampilan, Pemahaman, Menulis, Teks Berita